Superfícies imaginadas: fotografia, ruínas e iminências no sertão cearense - Rubens Venâncio (2017)
sought with this research to work with memory in its poetic manifestations through photography, from the creation of the photographic essay "imminences", realized in three places of Ceará and composed of two collections: "place-ruin" and "place-memory". For that, I adopted the idea of "memorymontage", as well as a conceptual and artistic doing that intertwined memory, forgetfulness and ruin.By mapping particularities and problems in Baixio das Palmeiras, Baixio do Múquem and Cococi, I identify two scenarios that guided the visual investigation and were therefore named: the first two begin to be photographed from the idea of "imminence of eviction" and the third idea of the "imminence of disappearance".The "place-memory" (collection made in digital format) are images of meaningful places pointed out by the residents and was a method to perceive through the photographicimaginative creation the relation with the space during the impositions of eviction and the scenario of disappearance. The "place-ruin" (made with large-format Polaroid film) sought to establish memories from the dramas of the habitants livingunderneath. In this context, I proposed what I called the bend between the ruin of photography and the ruin of life.How, with the photographic narrative and the proposed discussions, will arise a context that will involve individuals, memory and ruins? How can memory may emerge as a phenomenon through the poetic work of the image? How to build memories from the experience of forgetfulness? These questions functioned as north in this research.